2020
DOI: 10.2106/jbjs.19.00925
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Reduces the Rate of Periprosthetic Joint Infection After Aseptic Revision Arthroplasty

Abstract: Background: Revision total joint arthroplasty (TJA) has a higher rate of periprosthetic joint infection (PJI) compared with primary TJA, possibly as the result of increased allogeneic blood transfusion. Tranexamic acid (TXA) is gaining popularity in revision TJA to minimize blood loss and the need for transfusion; however, its effect on PJI reduction has yet to be investigated. The hypothesis of this study was that the administration of TXA during revision arthroplasty is protective against subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Due to the abovementioned relationship between preoperative anaemia and the development of PJI, more recently, blood conservation strategies have gained attention in the field of arthroplasty. Here, multiple studies have shown that reducing intraoperative blood loss by perioperative application of TXA reduces the risk for PJI after both primary and revision total joint arthroplasty [ 19 , 20 ]. While its effectiveness in reducing blood loss and thereby transfusion rates has been proven by several studies, its exact role in reducing this risk of infection has yet to be studied in depth.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the abovementioned relationship between preoperative anaemia and the development of PJI, more recently, blood conservation strategies have gained attention in the field of arthroplasty. Here, multiple studies have shown that reducing intraoperative blood loss by perioperative application of TXA reduces the risk for PJI after both primary and revision total joint arthroplasty [ 19 , 20 ]. While its effectiveness in reducing blood loss and thereby transfusion rates has been proven by several studies, its exact role in reducing this risk of infection has yet to be studied in depth.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of TXA significantly reduced postsurgery infection rates, as it controls bleeding through its antifibrinolytic effect ( 9 13 ). Infection rates were significantly lower among nondiabetic patients who received TXA during surgery ( P = 0.003) ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…It also seems to decrease infectious complication rates. Some authors point out that by reducing local hematoma, TXA could indirectly reduce infection rates ( 9 13 ). Whether, in addition to its antifibrinolytic action, TXA has a potential antibiotic effect, as demonstrated for hyaluronic acid ( 7 ), needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported to have a potential downregulating effect on postoperative infection. Clinical researchers have found that it reduces the infection rate after total joint arthroplasty 9 , which allows us to recognize the utilization of tranexamic acid in orthopaedic surgeries in addition to haemostasis.…”
Section: Discussionmentioning
confidence: 99%